2021
DOI: 10.3390/nu13124394
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Postoperative Coffee Consumption on Postoperative Ileus after Abdominal Surgery: An Updated Systematic Review and Meta-Analysis

Abstract: Background: Previous systematic reviews have not clarified the effect of postoperative coffee consumption on the incidence of postoperative ileus (POI) and the length of hospital stay (LOS). We aimed to assess its effect on these postoperative outcomes. Methods: Studies evaluating postoperative coffee consumption were searched using electronic databases until September 2021 to perform random-effect meta-analysis. The quality of evidence was assessed using the Cochrane risk-of-bias tool. Caffeinated and decaffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…The guidelines for postoperative cesarean section recommend a high intake of fruits and vegetables to prevent constipation ( 44 ). Moreover, a review published in 2021 showed that postoperative coffee consumption can likely reduce POI incidence after a cesarean section ( 20 ). Nevertheless, no correlation was observed in this study between the consumption of fruits, vegetables or coffee and delivery mode after the other confounding factors, including residence, education, income, and dietary caregivers, were controlled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The guidelines for postoperative cesarean section recommend a high intake of fruits and vegetables to prevent constipation ( 44 ). Moreover, a review published in 2021 showed that postoperative coffee consumption can likely reduce POI incidence after a cesarean section ( 20 ). Nevertheless, no correlation was observed in this study between the consumption of fruits, vegetables or coffee and delivery mode after the other confounding factors, including residence, education, income, and dietary caregivers, were controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies found that women who had a cesarean section are offered oral fluids and food. Moreover, some studies determined that coffee can be given to patients to enhance the recovery of their gastrointestinal function after elective cesarean section ( 20 , 21 ). However, studies that investigated the association between vaginal delivery and postpartum diet are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Five systematic reviews and meta-analyses on this issue summarized in Table 3 were published recently. Each of them included between four and thirteen randomized control trials concerning both colorectal and gynecological interventions and compared coffee consumption either to water or to no intervention [113][114][115][116][117]. In the five meta-analyses, the time to first flatus was decreased by 3.6 to 10 h. The delay before the first bowel sound was reduced by 3.3 to 12.09 h. The time before first defecation was significantly affected, with reductions ranging from 9.4 to 16.1 h in the coffee group compared to controls.…”
Section: Effects Of Coffee After Abdominal Surgerymentioning
confidence: 99%
“…The most recent review and meta-analysis on postoperative ileus was published at the end of 2021 [117] and included 13 trials concerning colorectal surgeries, cesarean sections, and gynecologic surgeries on a total of 1246 patients. The data from this review are in agreement with the previous ones, and in addition, this review reported a statistically significant reduction of the occurrence of postoperative ileus (RR = 0.42; 95% CI, 0.26-0.69).…”
Section: Effects Of Coffee After Abdominal Surgerymentioning
confidence: 99%
“…Early refeeding as soon as patient wakes up is encouraged and reduces the length of stay and complications. However, early refeeding can lead to more vomiting if it is not accompanied by systematic prevention of postoperative nausea and vomiting as well as multimodal management of paralytic ileus by stimulating early mobilization, reducing fluid intake intravenously, using oral laxatives (for example Magnesia San Pellegrino® twice a day), or even stimulating coffee consumption [33].…”
Section: Postoperativementioning
confidence: 99%